Cryptography of Java Language Using Basa Walikan Methods in Yogyakarta - Wintolo, Hero; Pujiastuti, Asih; Astuti, Ellyana Mega Dewantri (Sekolah Tinggi Teknologi Adisutjipto, 2019)
Basa Walikan can be used as one of the methods in cryptography because the Basa Walikan character exchange process is not easily understood by all people who can speak Javanese. Basa Walikan used in this research is Basa-Walikan in Yogyakarta, which is sourced from Javanese script characters written in a two-line countdown rule. In Roman characters it becomes ha, na, ca, ra, ka, da, ta, sa, wa, la, pa, dha, ja, yes, nya, ma, ga, ba, tha, nga. The characters in Javanese script are written in 4 (four) lines. The process of character reversal in Basa Walikan uses the mechanism of the first line exchanged with the third line and the second line is swapped to the fourth line as well as the opposite. In this research software for message safety with Basa Walikan was made. From the White Box and Black Box test results it can be concluded that the encryption process and the description process are in accordance with the design of the application being made. If the word being tested is two consonants m and p that are close together, then the encryption process and the description process is done separately or by character.